Gambaran Insiden Bendungan Asi dan Upaya yang dilakukan Ibu untuk Mengatasinya - Netty Ami R. F Sihite; Riri Novayelinda; Widia Lestari (STIKes Payung Negeri Pekanbaru, 2022)
Introduction: Breast engorgement is a condition where there is swelling due to breast milk as a result of the ducts lactiferous which causes inhibition of breastfeeding. If not treated promptly, this condition can lead to further complications such as abscesses and mastitis of the breast. For this reason, appropriate efforts are needed to overcome breast engorgement that can be carried out by mothers. This research aims to identify a description of the incidence and the treatment made by mothers to overcome breast engorgement. Methods: The design of this research is descriptive quantitative research. Data were collected using observation sheets consisting of observations about the incidence of breast engorgement and the treatment made by mothers to overcome them. With 69 respondents who are breastfeeding mothers with children aged 0-10 months at the Puskesmas Rawat Inap Sidomulyo Pekanbaru. The data analysis used is a simple descriptive in the form of a frequency distribution table. Results: The results of this study showed 54 respondents (78.3%) had experienced breast engorgement and the most treatment made by mothers in overcoming breast engorgement were breast pumps as many as 27 respondents (39,1%). Conclusion: Overall it was locked that mothers aged 0-10 months at the Puskesmas Rawat Inap Sidomulyo Pekanbaru had experienced breast engorgement and the treatment made to breastfeed were breast pumps. This research is expected to contribute to the knowledge of the incidence of breastfeeding and the treatment that mothers can do to overcome it.